2008
DOI: 10.1007/s11999-008-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GDF-5 and Uniaxial Strain on Mesenchymal Stem Cells in 3-D Culture

Abstract: Recent endeavors in tissue engineering have attempted to identify the optimal parameters to create an artificial ligament. Both mechanical and biochemical stimulation have been used by others to independently modulate growth and differentiation, although few studies have explored their interactions. We applied previously described fabrication techniques to create a highly porous (90%-95% porosity, 212-300 lm), 3-D, bioabsorbable polymer scaffold (polycaprolactone). Scaffolds were coated with bovine collagen, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…This has been supported by recent findings demonstrating that several soluble growth factors, e.g. basic fibroblast growth factor [Sahoo et al, 2010], growth differentiation factor 5 (GDF-5) [Farng et al, 2008] and bone morphogenetic protein 12 (BMP-12 or GDF-7) [Wang et al, 2005;Violini et al, 2009], are able to induce tenogenic differentiation in MSCs. Among these, GDF-5, which is a member of the human BMP family, has been identified as a key biological molecule that can accelerate tendon healing [Aspenberg and Forslund, 1999].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…This has been supported by recent findings demonstrating that several soluble growth factors, e.g. basic fibroblast growth factor [Sahoo et al, 2010], growth differentiation factor 5 (GDF-5) [Farng et al, 2008] and bone morphogenetic protein 12 (BMP-12 or GDF-7) [Wang et al, 2005;Violini et al, 2009], are able to induce tenogenic differentiation in MSCs. Among these, GDF-5, which is a member of the human BMP family, has been identified as a key biological molecule that can accelerate tendon healing [Aspenberg and Forslund, 1999].…”
Section: Introductionmentioning
confidence: 62%
“…To overcome such issues, a number of tissue engineering approaches are presently being developed to induce tenogenic differentiation in human MSCs (hMSCs), or to produce controlled differentiation of hMSCs into the desired tenogenic lineage prior to transplantation. An example of such an approach is the use of growth factors [Farng et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, MSCs have been successfully induced into tenocytes by exposure to growth factors BMP-12 (Violini et al 2009) or low-dose FGF-2 (Hankemeier et al 2005). Meanwhile, GDF-5 has also been reported to increase mRNA expression of Col I and SCX in MSCs which are believed to be the markers of tendon/ligament differentiation (Farng et al 2008). Ouyang et al showed when assembled with frozen tendon graft in vitro, previously made MSCs sheets were wellincorporated within the tissue sheath around the tendon and adopted characteristic spindle-shaped morphology of tenocyte-like cells (Ouyang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Distinctively, mechanical measures were more recommended for tenogenic differentiation of MSCs than other phenotypes of differentiation. It has been demonstrated that cyclic mechanical stretch not only up-regulated mRNA level expression of tendon/ ligament-related genes such as Col I, Col III, TNC (Farng et al 2008;Chen et al 2008;Altman et al 2002;Lee et al 2007) but also was required for maintaining the expression of those tendon makers (Kuo and Tuan 2008). The MSCs-collagen sponges construct engineered tendon tissue subjected to cyclic mechanical stretch before transplantation has been demonstrated to significantly improve tendon repair and show better mechanical properties than control group (Juncosa-Melvin et al 2006).…”
Section: Introductionmentioning
confidence: 99%